(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
.In the summer of 1982 the last communal attempt by a Central Asian Turkic community, led by a capable traditional Khan, Haji Rahmanqul Kutlu, to reach Anatolia was accomplished. This event which involved over a thousand Kirghiz mobile herders, with a lifestyle resembling the “Stone Age”, may have marked the end of such journeys for the Turkic peoples of Central Asia coming to Anatolia which begun nearly a thousand years earlier. The Kirghiz from the Afghan Pamirs, however, were motivated by entirely different reasons. That is, running away from Communism (Soviets, Chinese and Afghan) for over a century to safeguard their Islamic faith and Kyrgyz identity and not searching for new pasturelands or extend the domain of Islam. Like their ancestors, these Pamir Kirghiz have not only strengthened their Islamic faith and Turkic identity, but they have also experienced unfathomable demographic, social, economic and cultural transformation during the last four decades of their lives in modern Turkiye. In this presentation, I will discuss their remarkable journey based on my anthropological field research among the Kyrgyz which began in 1972 in the Pamirs of Afghanistan.